Soropositividade ANTI PGL-I em contatos domiciliares de casos de hanseníase na microrregião de Almenara, Minas Gerais - Ana Paula Mendes Carvalho (2012)
Leprosy diagnosis is essentially clinical, based on the patients history and life conditionanalysis as well as on dermatological and neurological examinations. Complementaryexaminations can be performed as diagnosis confirmation and patient classification.Serological tests that identify antibodies to phenolic glycolipid-I antigen specific toMycobacterium leprae are being used to classify patients, monitor therapy, assess the riskof recurrence and select contacts at a greater risk of becoming infected. The aim of thepresent study is to analyse the anti PGL-I seropositivity in household contacts of notifiedleprosy cases in the micro region of Almenara, Minas Gerais. It is an analytic study with across-sectional design. Seven municipalities in the micro region of Almenara wereselected, since the area displayed the largest number of cases and household contactsregistered by the Sistema de Informação de Doenças de Notificação from 2006 to 2010.Inclusion criteria for household contacts were minimum age 7 years old, people with nohistory of leprosy living with the leprosy index case at the time of diagnosis. An IndividualNotification Form to identify leprosy cases. Data was collected during household visits.Data were obtained through a structured questionnaire. The ML Flow test was used forserological analysis. Epi Info was used to prepare database. Statistical Package for theSocial Sciences and Statistical Software for Professionals were applied for statisticalanalysis. The study was approved by the Ethics in Research Committee of theUniversidade Federal de Minas Gerais. The general rate of anti-PGL-I seropositivity was13.9%. Among contact cases classified as paucibacillary and multibacillary the rate was8.8% and 18.2%, respectively. There was a statistical association (p <0.05) between age,the presence of signs suggestive of leprosy and anti PGL-I seropositivity. Regarding theclinical features of index leprosy cases, the variables operational classification, clinicalform, and disability degree at diagnosis were significantly associated with the serologyof household contacts. In the final Poisson regression model age, presence of signssuggestive of leprosy and the index case operational classification remained associatedwith anti PGL-I seropositivity. The results indicate that the anti-PGL-I seropositivity ofhousehold contacts is related to the clinical features of leprosy cases and that serologicalevaluation could be used for identifying individuals at a higher risk of developing leprosyor in the early stages of the disease. Although the serological tests available are notconsidered as diagnostic tests, they can be used as secondary strategies, when associatedwith clinical parameters. This study highlights the importance of further serological studieson leprosy cases, mainly with a longitudinal design, to assess the progression and clinicalmanifestation of the disease as well as its relation to anti PGL-I serology.Descriptors: